Selective Electrochemical Reduction of Carbon Dioxide to Ethanol on a Boron‐ and Nitrogen‐Co‐doped Nanodiamond. Issue 49 (24th October 2017) - Liu, Yanming; Zhang, Yujing; Cheng, Kai; Quan, Xie; Fan, Xinfei; Su, Yan; Chen, Shuo; Zhao, Huimin; Zhang, Yaobin; Yu, Hongtao; Hoffmann, Michael R.
Abstract: Electrochemical reduction of CO2 to ethanol, a clean and renewable liquid fuel with high heating value, is an attractive strategy for global warming mitigation and resource utilization. However, converting CO2 to ethanol remains great challenge due to the low activity, poor product selectivity and stability of electrocatalysts. Here, the B‐ and N‐co‐doped nanodiamond (BND) was reported as an efficient and stable electrode for selective reduction of CO2 to ethanol. Good ethanol selectivity was achieved on the BND with high Faradaic efficiency of 93.2 % (−1.0 V vs. RHE), which overcame the limitation of low selectivity for multicarbon or high heating value fuels. Its superior performance was mainly originated from the synergistic effect of B and N co‐doping, high N content and overpotential for hydrogen evolution. The possible pathway for CO2 reduction revealed by DFT computation was CO2 →*COOH→*CO→*COCO→*COCH2 OH→*CH2 OCH2 OH→CH3 CH2 OH. Abstract : Efficient and selective electrochemical reduction of CO2 to ethanol was achieved on a nonmetallic B‐ and N‐co‐doped nanodiamond used as an electrocatalyst. The synergistic effect of co‐doping, N content, and H2 evolution potential were used as key factors for tailoring ethanol selectivity.